HUMAN RIGHTS AND THEIR CONTEXTUALIZATION: AFRICAN CHARTER ON HUMAN AND PEOPLE RIGHT OF 1981 - Calestino Victor Mussomar (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2020)
The aim of this article is to propose a theoretical reflection of the urgent contextualization of Human Rights in African countries. As we know, Human Rights are transversal, that every people are a consequence of historical, social and political contexts. This article tries to defend that it is possible to avoid Western imperialism in the name of Human Rights with its form of universalism. For Africa, the context of Ubuntu is a good alternative.